Efficient Acid-catalyzed (18)F/(19)F Fluoride Exchange of BODIPY Dyes - Keliher, Edmund J. (2014)
Fluorine containing fluorochromes represent important validation agents for PET imaging agents as they can be easily rapidly validated in cells by fluorescence imaging. In particular, the (18)F-labeled BODIPY-FL fluorophore has emerged as an important platform but little is known about alternative (18)F-labeling strategies or labeling on red shifted fluorophores. Here we explore the acid-catalyzed (18)F/(19)F exchange on a range of commercially available N-hydroxysuccinimidyl ester and maleimide BODIPY fluorophores. We show this method to be a simple and efficient (18)F-labeling strategy for a diverse span of fluorescent compounds, including a BODIPY modified PARP-1 inhibitor, and amine- and thiol-reactive BODIPY fluorophores.